2016
DOI: 10.1242/jeb.141424
|View full text |Cite
|
Sign up to set email alerts
|

Dietary flavonoids advance timing of moult but do not affect redox status of juvenile blackbirds (Turdus merula)

Abstract: Flavonoids are the most abundant plant polyphenols, widely occurring in fruits and berries, and show a strong antioxidant activity in vitro. Studies of avian species feeding on berries suggest that dietary flavonoids have health-promoting effects and may enhance the expression of melanin-based plumage traits. These effects are probably mediated by the antioxidant activity of flavonoids. However, the effect of dietary flavonoids on oxidative status has never been investigated in any bird species. We analysed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
1
2
0
Order By: Relevance
“…Our meta-analysis showed that moult intensity was the most sensitive to diet alterations. It is in line with individual results: a wellbalanced diet (Pap et al, 2008) and additional dietary flavonoids (Pap et al, 2009;Cecere et al, 2016) enhanced the process of feather renewal. Flavonoid-enriched food may facilitate pigment synthesis,…”
Section: Discussionsupporting
confidence: 85%
“…Our meta-analysis showed that moult intensity was the most sensitive to diet alterations. It is in line with individual results: a wellbalanced diet (Pap et al, 2008) and additional dietary flavonoids (Pap et al, 2009;Cecere et al, 2016) enhanced the process of feather renewal. Flavonoid-enriched food may facilitate pigment synthesis,…”
Section: Discussionsupporting
confidence: 85%
“…The following exclusion criteria were applied: i) studies that measured expression of antioxidant genes because I were interested in the biochemical differences between sexes; ii) studies that used metrics of free radical generation as an index of oxidative stress, since they do not provide direct evidence of oxidative stress (reactive species might be mopped up before oxidative damage is generated); iii) studies where necessary information for calculating effect size was unavailable. Overall, the final dataset included 732 effect sizes from 100 articles (82 species: 7 fish, 5 reptiles, 44 birds, and 26 mammals) (Almroth et al 2008; Alonso-Alvarez et al 2004a, 2004b; Barrera-García et al 2012; Beamonte-Barrientos and Verhulst 2013; Beaulieu and Schaefer 2014, Beaulieu et al 2010, 2011, 2014; Bertrand et al 2006; Bilham et al 2013; Bize et al 2008; Bonisoli-Alquati et al 2010; Canovas et al 2014; Casagrande et al 2011, 2012a, 2012b; Cecere et al 2016; Christensen et al 2015; Christie et al 2012; Cohen et al 2008; Costantini and Bonadonna 2010; Costantini and Dell’omo 2015; Costantini et al 2007, 2008, 2010, 2012a, 2012b, 2013, 2014, 2014a, 2014b; Costantini 2010; Cram et al 2015a, 2015b; Depboylu et al 2013; Ehrenbrink et al 2006; Emaresi et al 2016; Figueiredo-Fernandes et al 2006b; Georgiev et al 2015; Gomes et al 2014; Grunst et al 2014; Heiss and Schoech 2012; Herrera-Dueñnas et al 2014; Isaksson et al 2009, 2011, 2013; Isaksson 2013; Jolly et al 2012; Kamper et al 2009; Kanerva et al 2012; Kayali et al 2007; Kurhalyuk et al 2009; Langley-Evans and Sculley 2005; Leclaire et al 2015; Lilley et al 2014; Lopes...…”
Section: Methodsmentioning
confidence: 99%
“…Phenolic compounds have free radical scavenging abilities, anti-mutagenic and anti-carcinogenic activities and can reduce the risk of cardiovascular and carcinogenic diseases (Nakamura et al, 2003). Flavonoids are the most abundant plant polyphenols occurring in fruits with strong antioxidant activity and disease-preventing properties against cancer and cardiovascular diseases (Wang and Ho, 2009;Cecere et al, 2016). The various flavonoids like anthocyanins, ellagic acid derivatives and hydrolysable tannins (punicalagin, gallic and ellagic acid) are responsible for the antioxidant activity of pomegranate fruit and a very high antioxidant activity in the wild and cultivated pomegranate fruit extracts (peel, juice and seeds) have been observed by various researchers (Gill et al, 2000;Aviram et al, 2000;Singh et al, 2002;Thakur et al, 2018;Hamid et al, 2020a).…”
mentioning
confidence: 99%